A systematic review of diagnostic, prognostic, and risk blood and urine biomarkers of transplant-associated thrombotic microangiopathy - Schoettler, Michelle L.; Bhatt, Harshil; Vasu, Sumithira (Frontiers in Immunology, 2023)
Transplant-associated thrombotic microangiopathy (TA-TMA) is an increasingly recognized complication of allogeneic and autologous hematopoietic cellular therapy (HCT), associated with significant morbidity and mortality. Although the central drivers of the disease are thought to be endothelial damage and complement activation, no specific diagnostic biomarkers have been identified. TA-TMA is typically diagnosed using criteria comprised of non-specific clinical and laboratory features. Some patients will have a self-remitting course, but more than half develop multi-organ dysfunction or die, making prognostic biomarkers critical. Prevention of TA-TMA, an approach central to other HCT complications such as graft-versus-host disease, is largely untested in part due to a lack of identified early high-risk biomarkers. We conducted a systematic review to summarize the diagnostic, early risk, and prognostic biomarkers of TA-TMA. We screened the titles and abstracts of 1524 citations. After screening out duplications, we read the abstracts of 979 papers and fully reviewed 132 full-text publications. Thirty-one publications fulfilled the inclusion criteria of more than five patients with TA-TMA and a reported measure of association with diagnosis, prognosis, or risk of later development of the disease. Fourteen studies (45%) were with adults, 12 (39%) were with children <18 years old, three included both children and adults, and two did not report age. There were 53 biomarker or biomarker signature entries, and a total of 27 unique biomarkers. Only four biomarkers reported sensitivity and specificity. The single biomarker with the most robust data was sC5b-9, which conferred diagnostic, prognostic, and risk implications. Studies of combinations of biomarkers were rare. No meta-analyses were performed because of significant heterogeneity between studies. The limitations of studies included small sample size, study designs with a high risk of bias (i.e., case–control), the timing of sample collection, and the selection of controls. Furthermore, only two (6%) studies included a training and validation cohort. Cut-off points are needed to stratify groups, as most biomarkers do not have normal values, or normal values cannot be assumed in the HCT setting. In the future, multi-institutional, collaborative efforts are needed to perform rigorously designed, prospective studies with serially enrolled patients, with samples collected at the time of TA-TMA diagnosis, careful selection of controls, and validation of selected biomarkers and cut-off points in a separate cohort.